Las teorías científicas nacen como respuesta a problemas de la experiencia. Una objeción a Paul Thompson - Blanco, Daniel (2011)
This paper is about Paul Thompson’s position regarding the way in which the identity of scientific theories is determined, that is, excluding from the explication the intended applications of the community of users. Following this presentation, it shows how the inclusion of this set of applications in the theory identity, as recommended by the structuralist view of scientific theories, not only does not bear the problems Thompson wished to avoid, but also allows to see certain diachronic aspects of the theory that otherwise would go unnoticed.